Perubahan Sistem Pemerintahan Kadaleman Kawasen Mendadi Desa Kawasen (1628-1811 M.) - Fadilah, Fadilah; Brata, Yat Rospia; Budiman, Agus (Faculty of Teacher Training and Education, 2023)
ABSTRACTIn the 16th century, Kadaleman Kawasen became one of the government systems that was influenced by Mataram. The change of the kadaleman system into a village was influenced by colonial policies that spread its power to Priangan. This study aims is to describe the process of changing the Kadaleman Kawasen government system into a village named Kawasen Village and to describe the comparison of the two systems. The method is using the historical method with for steps. The first is heuristic, it means the source collection stage. The second is criticism, it means researching the source, criticism is divided into external critism and internal criticism. The third is interpretations, it means interpreting the source and the fourth is historiography, it means writing of history. Kadaleman Kawasen that had a district level position was abolished by the colonial government for some reason. Kadaleman Kawasen runs a government system under the reign of the Mataram Kingdom hegemony. The regent gains the position and power as a minor king who reigns in his territory with inherent privilages. While the Village Government systems was from changes in colonial policies that became their superiors. The form and structure of government is determined based on the customary law of each region. Keywords: Government, Kadaleman, Kawasen, and Village